Potential of Integrated [18F] Fluorodeoxyglucose Positron-Emission Tomography/CT in Identifying Vulnerable Carotid Plaques - Kwee, R.M.; Truijman, M.T.B.; Mess, W.H.; Teule, G.J.J.; ter Berg, J.W.M.; Franke, C.L.; Korten, A.G.G.C.; Meems, B.J.; Prins, M.H.; van Engelshoven, J.M.A.; Wildberger, J. E.; van Oostenbrugge, R.J.; et al. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: There is a need for improved risk stratification of patients with TIA/stroke and carotid atherosclerosis. The purpose of this study was to prospectively investigate the potential of integrated 18F-FDG PET/MDCT in identifying vulnerable carotid plaques. MATERIALS AND METHODS: Fifty patients with TIA/stroke with an ipsilateral carotid plaque causing <70% stenosis and a plaque on the contralateral asymptomatic side underwent integrated 18F-FDG PET/MDCT within 36.1 ± 20.0 days (range, 9–95 days) of the last symptoms. Carotid plaque 18F-FDG uptake was measured as both the mean and maximum blood-normalized SUV, known as the TBR. Using MDCT, we assessed volumes of vessel wall and individual plaque components. RESULTS: Mean TBR was only significantly larger in the ipsilateral plaques of patients who were imaged within 38 days (1.24 ± 0.04 [SE] versus 1.17 ± 0.05, P = .014). This also accounted for maximum TBR (1.53 ± 0.06 versus 1.42 ± 0.06, P = .015). MDCT-assessed vessel wall and LRNC volumes were larger in ipsilateral plaques of all patients (982.3 ± 121.3 versus 811.3 ± 106.6 mm3, P = .016; 164.7 ± 26.1 versus 134.3 ± 35.2 mm3, P = .026, respectively). CONCLUSIONS: In the present study, 18F-FDG PET only detected significant differences between ipsilateral and contralateral asymptomatic plaques in patients with TIA/stroke who were imaged within 38 days, whereas MDCT detected larger vessel wall and LRNC volumes, regardless of time after symptoms. In view of the substantial overlap in measurements of both sides, it remains to be determined whether the differences we found will be clinically meaningful. CEAcarotid endarterectomyCVcoefficient of variation18F-FDG[ 18F] fluorodeoxyglucoseICCintraclass correlation coefficientLRNClipid-rich necrotic coreMDCTmultidetector row spiral CTNASCETNorth American Symptomatic Carotid Endarterectomy TrialPETpositron-emission tomographySEstandard errorSUVstandardized uptake valueTBRtarget-to-background ratioTIAtransient ischemic attack